The Correlation of Parents' Education Level and Chil Care Pattern of Pre School Children 3 to 6 Years Old in RA Tarbiyatussibyan Tanjung Kalidawir Tulungagung - Yeni Kartika Sari; Unifatus Zahro (Journal of Ners and Midwifery, 2017)
Child care pattern is very important in the development of children, especially in overcoming emotional development. The education level of parents is expected to affect the way parents provide for their children's upbringing. This study aims to determine the relationship between the level of parental education with child care pattern of pre-school children in RA Tarbiyatussibyan Tanjung Kalidawir Tulungagung. This research is an observational analytic research with cross sectional approach. The independent variable in this study is the level of parental education. While the dependent variable is the child care pattern of pre school children. The population in this study is all parents of pre school children that are 86 people. While the sample are all the population who meet the inclusion criteria which amounted to 72 respondents. The collected data will be analyzed using Wilcoxon Sign Rank Test with significance value of 0.05. Based on the research results obtained value (Î±) count of 0.000. Because the value of Î± <0,05, So it can be concluded that there is a significant relationship between the level of parental education with the child care pattern of pre-school children in RA Tarbiyatussibyan Tanjung Kalidawir Tulungagung. It is suggested to nurse as educator to provide health education about child care pattern and its impact on child growth in pre-school education.